(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2025)
Additive manufacturing (AM) offers significant potential for the design of medical phantoms used in quality assurance for medical imaging and treatment planning. This study presents the design and fabrication of a head and neck phantom for computed tomography (CT) quality assurance. Appropriate infill densities of Polylactic acid (PLA) were selected to achieve tissue-equivalent CT values, enabling the integration of many anatomical structures in the head and neck region. A bone surrogate material was incorporated post-processing to achieve high density values that are unachievable with common 3D printing materials. CT validation confirmed the phantom’s ability to replicate appropriate Hounsfield unit (HU), demonstrating its suitability for imaging-based assessments. This phantom provides a reproducible and customizable solution for treatment verification in head and neck cancer therapies.